Irreversible Anterior Ischemic Optic Neuropathy Complicating Interferon Alpha and Ribaverin Therapy. (9th December 2010) - Seddik, Hassan; Tamzaourte, Mouna; Rouibaa, Fadoua; Fadlouallah, Maha; Benkirane, Ahmed
Abstract : Ophthalmologic complications with interferon therapy are rare and usually reversible. The anterior ischemic optic neuropathy is an uncommon complication of interferon treatment. A case of irreversible anterior ischemic optic neuropathy complicating interferon therapy for chronic hepatitis C is reported. We suggest that periodic ophthalmological examinations, including visual acuity and fundus examinations, should be performed to patients with high risk of ocular complications after starting and during treatment. We also suggest that an ophthalmologist would be able to detect these complications. Antiviral treatment should be stopped immediately if severe ophthalmologic complications occur.